2019
DOI: 10.1071/sh18104
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the geospatial barriers to antiretroviral initiation, adherence and viral suppression among people living with HIV

Abstract: Background With the emergence of antiretroviral therapy (ART), Treatment as Prevention (TasP) has become the cornerstone of both HIV clinical care and HIV prevention. However, despite the efficacy of treatment-based programs and policies, structural barriers to ART initiation, adherence and viral suppression have the potential to reduce TasP effectiveness. These barriers have been studied using Geographic Information Systems (GIS). While previous reviews have examined the use of GIS for HIV testing – an essent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…Most of the research examining the relationship between discrimination based on race/ethnicity and health outcomes focuses primarily on urban and suburban populations, but some of the same implications are applicable to rural areas. As an example, a recent review of Antiretroviral therapy (ART) initiation delays found racial segregation and, to some extent, rural residence, associated with delayed initiation of care and subsequent adherence [53]. The interplay of social segregation and discrimination and health in rural settings is generally complex [54,55].…”
Section: Racism and Ethnocentrismmentioning
confidence: 99%
“…Most of the research examining the relationship between discrimination based on race/ethnicity and health outcomes focuses primarily on urban and suburban populations, but some of the same implications are applicable to rural areas. As an example, a recent review of Antiretroviral therapy (ART) initiation delays found racial segregation and, to some extent, rural residence, associated with delayed initiation of care and subsequent adherence [53]. The interplay of social segregation and discrimination and health in rural settings is generally complex [54,55].…”
Section: Racism and Ethnocentrismmentioning
confidence: 99%
“…Tian et al [ 7 ] have analyzed the impact of urbanization on the prevalence of scarlet fever. Card et al [ 8 ] reviewed the application of geographic information systems in HIV and emphasized the need for careful planning of resources concerning the geospatial movement and location of people living with HIV. Therefore, this study uses a Bayesian spatiotemporal model to analyze the impact of relevant data on the spatiotemporal distribution of HIV in Luzhou from 2011 to 2020 and provide a point of reference for the precise prevention and control of HIV in other prefecture-level cities in southwest China.…”
Section: Introductionmentioning
confidence: 99%
“…A recent review highlighted the geospatial variation in ART success and inequitable distribution of HIV care in racially segregated, economically disadvantaged, and increasingly rural areas [ 123 ]. It also highlighted the utility and limitations of using GIS to monitor health and HIV treatment outcomes and the need for careful planning of resources with respect to the geospatial movement and location of PLWH [ 123 ]. Many studies in this review in part or wholly used composite scores to describe neighborhood characteristics.…”
Section: Discussionmentioning
confidence: 99%